Cloning of the shark Po promoter using a genomic walking technique based on the polymerase chain reaction. - Fors, L (1990)
We have cloned the putative shark promoter of protein zero (Po) using a novel application of the ligation mediated single-sided polymerase chain reaction (PCR) method. This method uses linker ligation and subsequent amplifications with a linker primer and multiple specific primers to generate specificity. The method allowed us to amplify approximately 305 base pairs of shark genomic DNA sequence immediately upstream from the 5' end of our full-length Po cDNA. The Po promoter was shown to be directly linked to its first exon, contain a transcription initiation start site and sequences commonly found in eukaryotic promoters. This genomic walking technique will be useful for cloning promoters, insertion sites, and other sequences of interest without the need for constructing and screening genomic libraries.